Fear thy neighbor - Michaels, Fern (Kensington Publishing Corp., 2022)
After years of drifting from one small Florida town to another, Allison Marshall believes she's found the ideal place to settle down on Palmetto Island, but soon discovers that the locals have a dark secret, and she must either stay and join them or risk escaping.